Low-voltage current mode power factor function generator - Kumwachara, Kiattisak; Fujii, Nobuo (My University, 2000)
This paper proposes a realization of power factor function generator having an arbitrary base and power factor which are determined by the ratios of the currents provided from outside of the circuit. The circuit characteristics do not depend on any transistor parameters, temperature, and other environmental conditions. The circuit operation is based on current mode that has a capability of low power supply voltage operation below than 2.0V. SPICE simulation has been carried out using 0.7 μm BiCMOS parameters and shows quite good transfer characteristics.
Keywords: Current-mode circuit; Function generator; Low voltage circuit